2020
DOI: 10.5534/wjmh.190062
|View full text |Cite
|
Sign up to set email alerts
|

Role of Yoga in the Management of Premature Ejaculation

Abstract: Premature ejaculation (PE) is a common male sexual problem. Various non-pharmacological and pharmacological treatment options are available currently. The importance of yoga in the management of various sexual dysfunctions is increasingly recognized. In this review, we are analyzing the role of yoga in the management of PE. This paper explores the mechanism of yoga practices in the management of PE and the recommended yoga practice for PE. It also discusses the scientific evidence of yoga practices, such as yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Further, seven review studies (Table 2) provide evidence that yoga may be an alternative therapy for men with PE and other sexual dysfunctions. Four other studies [19][20][21][22] mainly discussed the mechanism and benefits of some yoga poses, pranayama, and breathing techniques that improve PE, sex life, and performance. Finally, three articles were reviewed and highlighted the effect of yoga intervention on infertility [23][24][25]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, seven review studies (Table 2) provide evidence that yoga may be an alternative therapy for men with PE and other sexual dysfunctions. Four other studies [19][20][21][22] mainly discussed the mechanism and benefits of some yoga poses, pranayama, and breathing techniques that improve PE, sex life, and performance. Finally, three articles were reviewed and highlighted the effect of yoga intervention on infertility [23][24][25]…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, yoga was found to increase sperm count, motility, prostate secretion, and overall sexual function, making it a valuable tool for reproductive health [20,24,25]. The study explored the benefits of yoga intervention in adults with infertility and assessed the effects through fertility rates and outcomes of assisted reproductive technology (ART).…”
Section: Discussionmentioning
confidence: 99%
“…PE is a common male sexual dysfunction that has a negative impact on patients' lives, including psychological and mental health, as well as interpersonal relationships with partners. 23,24 Despite this, this is one of the most neglected areas, presenting an unmet need for treatment. In recent years, with the application of SSRIs in clinic, it has opened up a new way for drug therapy of PE.…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, one study reported that 12 weeks of yoga increased IELT, although fluoxetine was more effective than yoga with more adverse effects [ 58 ]. Proposed mechanisms for the benefit of yoga in PE are improved neuro-psycho-physiological functioning, hormonal regulation, reduced sympathetic and increased parasympathetic activity, increased serum serotonin levels, pelvic floor muscle strengthening, improved body awareness (and ejaculatory control), and management of underlying psychological or physical risk factors [ 92 ]. Furthermore, yoga has positive effects in relieving depression, anxiety and stress [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%